Implementasi Standar Sarana Dan Prasarana Pendidikan Dalam Mendukung Mutu Pembelajaran Di SMA Masa Depan Sleman Depok Yogyakarta - Dinda Agustiana; Sedya Santosa; Ismail; Andika Febriyanto (Yayasan Al-Afif, 2026)
Educational facilities and infrastructure are strategic factors that influence the quality of the learning process. However, the successful implementation of educational facility and infrastructure standards is determined not only by the availability of facilities but also by the effectiveness of their management in supporting learning activities. This study aims to analyze the implementation of educational facilities and infrastructure standards at SMA Masa Depan Sleman Depok Yogyakarta, identify the supporting and inhibiting factors affecting their implementation, and examine their contribution to the quality of learning. This research employed a qualitative approach with a case study design. Data were collected through semi-structured interviews, observations, and documentation involving eight informants selected using purposive sampling. Data were analyzed using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of educational facilities and infrastructure standards has been carried out effectively through the provision of adequate learning facilities and systematic management processes, including planning, procurement, utilization, maintenance, and evaluation. The implementation was supported by the commitment of the school principal, the involvement of teachers and educational staff, and a well-structured management system. Meanwhile, the main challenges included budget limitations, the need for technological upgrades, and the continuous maintenance of facilities. The study further demonstrates that effectively managed educational facilities and infrastructure contribute significantly to improving learning effectiveness, student engagement, and the creation of a conducive learning environment. These findings highlight that systematic facilities and infrastructure management is a crucial factor in enhancing learning quality and achieving educational goals.